2023
DOI: 10.1001/jamaoto.2023.1473
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Interventions for Head and Neck Cancer–Associated Lymphedema

Abstract: ImportanceHead and neck cancer–associated lymphedema (HNCaL) affects up to 90% of survivors of head and neck cancer and is a substantial contributor to disability following head and neck cancer treatment. Despite the prevalence and morbidity associated with HNCaL, rehabilitation interventions are not well studied.ObjectiveTo identify and appraise the current evidence for rehabilitation interventions in HNCaL.Evidence ReviewFive electronic databases were searched systematically from inception to January 3, 2023… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Two recent systematic reviews of treatment for HNL have found CDT is most widely used in clinical practice [24,25 ▪▪ ]. CDT combines MLD with skincare, physical exercise and compression garments [24].…”
Section: Part 3: Complete Decongestive Therapy As An Intervention For...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent systematic reviews of treatment for HNL have found CDT is most widely used in clinical practice [24,25 ▪▪ ]. CDT combines MLD with skincare, physical exercise and compression garments [24].…”
Section: Part 3: Complete Decongestive Therapy As An Intervention For...mentioning
confidence: 99%
“…CDT combines MLD with skincare, physical exercise and compression garments [24]. Other interventions found in the literature include studies of selenium compounds and amifostine, low-level laser therapy, pneumatic compression, acupuncture, liposuction, kinesiotape and microvascular surgery [24,25 ▪▪ ]. However, as these are not under the scope of this article, they will not be discussed further here.…”
Section: Part 3: Complete Decongestive Therapy As An Intervention For...mentioning
confidence: 99%